Optimization of Artificial Intelligence to Address Injustice in Bankruptcy Requirements between State-Owned - Naek Mampetua Siringoringo (Publikasi Indonesia, 2024)
Injustice in bankruptcy requirements between State-Owned Enterprises and private companies creates legal uncertainty and unfair treatment in restructuring processes. State-Owned Enterprises often receive more protection compared to private companies, even though both are subject to Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. Article 2 paragraph (5) of this law stipulates that bankruptcy petitions against State-Owned Enterprises operating in the public interest can only be filed by the Minister of Finance, resulting in unequal legal treatment and raising questions about fairness in the bankruptcy system in Indonesia. This disparity negatively impacts business competition and public trust in the legal system. The purpose of this study is to analyze the injustice in bankruptcy requirements between State-Owned Enterprises and private companies, as well as to explore how artificial intelligence can be integrated to address these issues. The research method used is normative juridical, using a statutory approach and an analytical approach. The research findings indicate that the injustice in bankruptcy requirements is primarily caused by the differing legal treatment and policies that favor State-Owned Enterprises. The utilization of AI in bankruptcy data analysis and decision-making can assist in identifying patterns of injustice and provide more equitable and transparent recommendations. Artificial intelligence has the potential to address injustices in bankruptcy requirements between state-owned enterprises and private companies by enhancing transparency, accuracy, and fairness in legal processes. Its implementation requires clear regulatory support and collaboration among the government, legal institutions, and the private sector.